Effect of anions on the oxidation and reduction of hydrogen peroxide on the gold nanoparticle-deposited carbon fiber paper electrode. (20th October 2015) - Lin, Chen-Han; Wei, Lan-Yi; Lee, Jhao-Hong; Lien, Chun-Lung; Lu, Chung-Hsiang; Yuan, Chiun-Jye
Abstract: The nanostructured gold has been shown to catalyze the oxidation of hydrogen peroxide (H2 O2 ), an important analyte for clinical diagnosis. However, little is known about the effect of anions on its catalytic activity. In this study the gold nanoparticles (AuNP) of average size of 30-80 nm were electrodeposited on the carbon fiber paper (CFP) electrode to explore the effect of anions, such as phosphate, sulfate, nitrate, acetate, chloride and hydroxide ions, on the AuNP-catalyzed H2 O2 -oxidation. In phosphate solution the AuNP-deposited CFP (AuNP/CFP) exhibited high catalytic activity to H2 O2 . However, the catalytic activity of AuNP was severed blocked in solutions containing chloride, sulfate, nitrate, and acetate ions. Although hydroxide was shown to facilitate the catalysis of AuNP, the oxidation of H2 O2 was greatly interfered by the gold oxide formation in 0.05 M NaOH. A strong dipole moment between adsorbed anions, such sulfate, nitrate and acetate, and AuNP is suggested to block the access of H2 O2 molecules to the surface of AuNPs. This postulation is demonstrated by the finding that the electrochemical active surface area of AuNP/CFP is 0.90 ± 0.02 cm 2, 0.79 ± 0.08 cm 2, 0.66 ± 0.09 cm 2, 0.45 ± 0.04 cm 2, 0.42 ± 0.08 cm 2 and 0.15 ± 0.08 cm 2, in 0.05 M hydroxide, phosphate, bicarbonate, nitrate, acetate and sulfate solutions, respectively. These results indicate that the microenvironment near the surface of nanostructured Au is important to determine the catalytic activity of Au to H2 O2 .